2019
DOI: 10.1159/000502175
|View full text |Cite
|
Sign up to set email alerts
|

Registered Nurses’ Perception about Pain Management of Hospitalized Patients in One of the Governmental Hospitals in Dubai, UAE: A Cross-Sectional Study

Abstract: <b><i>Background:</i></b> Chronic and acute pain are highly prevalent, especially among hospitalized surgical patients, patients with cancer, and general medical inpatients. More than 50% of patients experience significant pain. Health professionals’ knowledge and attitude concerning pain management have often been referred to as insufficient. This study explored the attitudes and knowledge of nurses working in one of the government hospitals in the UAE, with regard to pain management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A positive association was reported between workload and nurses' tendency to perceive analgesic administration as fast-acting in comparison to NPPCM (Lucas & Bevan, 2020). Moreover, the workload can negatively impact nurses' practices in using NPPCM by hindering them from attending pain management classes (Abu baker et al, 2019), which subsequently leads to poor knowledge and negatively impacts the utilization of NPPCM (Adams et al, 2020). On the other hand, a study by Uysal and Yilmazer (2021) reported poor utilization of NPPCM due to the lack of time associated with the workload.…”
Section: Theme (3): Barriers Due To Patient Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive association was reported between workload and nurses' tendency to perceive analgesic administration as fast-acting in comparison to NPPCM (Lucas & Bevan, 2020). Moreover, the workload can negatively impact nurses' practices in using NPPCM by hindering them from attending pain management classes (Abu baker et al, 2019), which subsequently leads to poor knowledge and negatively impacts the utilization of NPPCM (Adams et al, 2020). On the other hand, a study by Uysal and Yilmazer (2021) reported poor utilization of NPPCM due to the lack of time associated with the workload.…”
Section: Theme (3): Barriers Due To Patient Factorsmentioning
confidence: 99%
“…Despite robust evidence of their benefits, NPPCM remains underutilized in clinical practice. Studies reveal nurses often have unfavorable attitudes about using NPPCM, stemming from knowledge gaps (Abu baker et al, 2019). Even nurses with adequate knowledge exhibit reluctance to adopt NPPCM into routine care (Jira et al, 2020; Zeleke et al, 2021).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation